Study of physical function in adolescents with haemophilia: The SO‐FIT study. Issue 6 (14th August 2017) - Khair, K.; Holland, M.; Bladen, M.; Griffioen, A.; McLaughlin, P.; von Mackensen, S.; ,
Abstract : Introduction: Contemporary haemophilia care demands Patient‐Reported Outcomes. SO‐FIT is a UK multi‐centre study, assessing self‐reported function, health‐related quality of life (HRQoL) and joint health in boys with severe haemophilia. Methods: Subjective physical function (PedHAL, HEP‐Test‐Q) and HRQoL (Haemo‐QoL Short Form [SF]) were assessed alongside joint health using the objective Haemophilia Joint Health Score (HJHS v2.1). Demographic and clinical data were collected. Results: Data from 127 boys mean age 12.38 ± 2.5 (range 8‐17) treated at 16 sites were analysed. One‐hundred‐and‐thirteen had haemophilia A, 25/9 past/current inhibitor, 124 were treated prophylactically (46.8% primary) and three on‐demand. In the preceding 6 months, boys reported median 0 joint bleeds (range 0‐8) with a median HJHS score of 1 (range 0‐30). Boys reported good physical functioning; HEP‐Test‐Q (M = 80.32 ± 16.1) showed the highest impairments in the domain "endurance" (72.53 ± 19.1), in PedHAL (M = 85.44 ± 18.9) highest impairments were in the domains "leisure activities & sports" (M = 82.43 ± 23.4) and "lying/sitting/kneeling/standing" (M = 83.22 ± 20.3). Boys reported generally good HRQoL in Haemo‐QoL SF SF (M = 22.81 ± 15.0) with highest impairments in the domains "friends" (M = 28.81 ± 30.5) and "sports & school" (M = 26.14 ± 25.1). HJHS revealed low correlations with the Haemo‐QoL SF ( r  = .251, P  < .006), the PedHAL ( r  = −.397, P  < .0001) and the HEP‐Test‐Q ( r  = −.323, P  < .0001). A moderate correlation was seen between HEP‐Test‐Q and Haemo‐QoL SF of r  = −.575 ( P  < .0001) and between PedHAL and Haemo‐QoL SF r  = −.561 ( P  < .0001) implying that good perceived physical function is related to good HRQoL. Conclusions: The SO‐FIT study has demonstrated that children with severe haemophilia in the UK report good HRQoL and have good joint health as reflected in low HJHS scores.